SERTIFIKAT CACAT HUKUM DALAM HUKUM PERTANAHAN DI INDONESIA - Khairina, Khairina (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2014)
Getting licence of land had great relation with the law of the land. Filling the form of land owner to Natinal Land Committee (BPN) where the land is located would give the great one’s position as the owner. The committee later on might give a land certificate to the owner. This certificate would be the fact by the owner when they faced any law problems. This certificate could be as a fact by the owner if there was no complain from other people who might claim the land as their land. However, if there was a complain to the validity of the land certificate, this certificate might become to premature certificate.